Tufts University 1980-81 women's swimming team - Unknown (Tufts Archival Research Center, 2008)
8x10; Front, left to right: Lisa Griffin, Sue Burt, Riva Levinson, Veroinca Karp, Capt. Kathy Elliot, Capt. Anne Twitchell, Julia Malloy, Donna Elmy, Mel Maloney, Liz Lottes. Second row: Roberta Goldstein, Treacy Moran, Ann Stafford, Laurie Rosenbaum, Lori Halivopoulos, Bev Walker, Katie Hannigan, Erin Donovan, Claudia Stearns. Third row: Jamie Grecean, Diving Coach, Maragaret Casey, Mary Howard, Pam Penton, Brenda Kay, Kathy Conley, Betsy Wells, Sue Decker, Julie Perpich, Heidi Ebel, Karen Kagan, Mary Kay Finnerty, Head Coach.